Phytophthora palmivora Relationship Analysis on ITS rDNA Primers Using MEGA11 Software (NCBI DNA Sequencing Library Study) - Rani Yosilia; Auliana Afandi; Ade Lenty Hoya; Christy Nur Cahyani; Ayaka Hieno (Departement of Agrotechnology, Agriculture Faculty, Universitas Lampung, 2024)
Phylogenetic study of Phytophthora palmivora species utilizing nucleotide sequences of rDNA ITS and genes was conducted to evaluate the cladistics and evolution of kinship among P. palmivora species in order to support genetic diversity and linkages and also compare with sequences of mitochondrial COX1. The analysis included 61 nucleotide sequences of P. palmivora rDNA ITS and one outgroup as well as 56 nucleotides sequences of COX1 retrieved from the NCBI GeneBank, which were aligned and trimmed using MEGA 11 software. The Kimura-2 parameter model and Maximum-Likelihood approach were used to create a monophyletic tree with four major clades. The percentage of GC content in DNA sequences was less than 50%, influencing genetic diversity and adaptation throughout evolutionary time periods. Temperature, humidity, rainfall, soil moisture, and seasonal fluctuations all work together to generate optimal climatic and weather conditions for the establishment and development of Phytophthora palmivora in tropical climates.